Microstructure and mechanical properties of GTAW welded joints of AA6105 aluminum alloy (2016)
Gas Tungsten Arc Welding (GTAW) is one of the most used methods to weld aluminum. This work investigates the influence of welding parameters on the microstructure and mechanical properties of GTAW welded AA6105 aluminum alloy joints. AA6105 alloy plates with different percent values of cold work were joined by GTAW, using various combinations of welding current and speed. The fusion zone, in which the effects of cold work have disappeared, and the heat affected zone of the welded samples were examined under optical and scanning electron microscopes, additionally, mechanical tests and measures of Vickers microhardness were performed. Results showed dendritic morphology with solute micro- and macrosegregation in the fusion zone, which is favored by the constitutional supercooling when heat input increases. When heat input increased and welding speed increased or remained constant, greater segregation was obtained, whereas welding speed decrease produced a coarser microstructure. In the heat affected zone recrystallization, dissolution, and coarsening of precipitates occurred, which led to variations in hardness and strength.